Living on wilderness time - Walker, Melissa (University of Virginia Press, 2002)
"Soon after her fiftieth birthday, Melissa Walker set out on a journey that many women of her generation have mapped only in their dreams. Having spent her adult life raising children and climbing the academic ladder, Walker decided to put some of the environmental theories she'd taught into practice. Leaving her suburban life, she ventured into the wilderness."